Recovering the counterfactual wage distribution with selective return migration - Costanza Biavaschi (Institute for the Study of Labor (IZA), 2012)
This paper explores the distribution of immigrant wages in the absence of return migration from the host country. In particular, it recovers the counterfactual wage distribution if all Mexican immigrants were to settle in the United States and no out-migration of Mexican-born workers occurred. Because migrants self-select in the decision to return, the overarching problem addressed by this study is the use of an estimator that accounts also for selection on unobservables. I adopt a semiparametric procedure that recovers this counterfactual distribution and find that Mexican returnees are middle- to high-wage earners at all levels of educational attainment. The presented results contrast with the general perception that those migrants who return home have failed in the host country.
Keywords: J61; F22; 330; return migration; self-selection; assimilation; U.S.-Mexico migration